On Samuelson Submanifolds in Four Space - Cooper, J.B.; Russell, T. (Інститут математики НАН України, 2009)
The object of study in this talk is a general class of submanifolds of R^4. The motivation for this work was the derivation of the following equation which answered a question posed by the distinguished economist P.A. Samuelson.